EFFECT OF FIBROIN SPONGE ON ALVEOLAR BONE REMODELING PROCESS POST TOOTH EXTRACTION - Sartika Puspita; Lutfia Siti Hanifatunnisa; Agustin Wulan Suci Dharmayanti; Erlina Sih Mahanani; Edwyn Saleh (Odonto : Dental Journal, 2022)
Background: There are still quite a lot of cases of tooth extraction in Indonesia because of the cavities are not treated or because of other cases. Extraction is the main cause of 90% of bone destruction and a risk of infection and bleeding. Fibroin sponge is a natural polymer material derived from Bombyx mori silk cocoon which contains of 18 amino acids and have a good mechanically, biodegradable and biocompatible. This study aimed to determine the effect of fibroin sponge on the remodeling of post tooth extraction sockets.Method: This study was a laboratory experiment with quasy experimental design using 30 Sprague dawley rats divided into 2 groups. Each group had the mandibular left incisor extracted. The first group as a control was given 15 ug of Curaspon and the second group was given 15 ug of fibroin sponge intra alveolar.Result: The results were observed after the 3rd, 7th, 14th, 21st, 28th days under a light microscope and identified by scoring bone remodeling based on predetermined criteria. Data were analyzed using the Mann-Whitney Test followed by the Kruskall-Wallis Test. The results showed that there was no difference in the process of bone remodeling post tooth extraction in the fibroin sponge group compared to Curaspon (p>0.05).Conclusion: Fibroin sponge has the same effect on the bone remodeling process as Curaspon.